2007
DOI: 10.1177/0013164407308469
|View full text |Cite
|
Sign up to set email alerts
|

Testing for Multigroup Invariance of the Computer Anxiety Scale

Abstract: The Computer Anxiety Scale (CAS) measures the perceptions of individuals with respect to their anxiety toward computers. Although the CAS was developed a number of years ago, research has shown that its factor structure has remained stable. Recent cross-cultural studies using samples of college students from various countries have also shown that the construct of computer anxiety as measured by the CAS has not changed. The present study uses structural equation modeling techniques to examine whether the CAS re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…Such an unconstrained model serves as the baseline model. Next, the model is estimated by constraining all the paths to be equal across groups [75]. The constrained model can be seen as a nested model of the baseline model.…”
Section: Tests Of Moderating Effectsmentioning
confidence: 99%
“…Such an unconstrained model serves as the baseline model. Next, the model is estimated by constraining all the paths to be equal across groups [75]. The constrained model can be seen as a nested model of the baseline model.…”
Section: Tests Of Moderating Effectsmentioning
confidence: 99%
“…In order to examine RQ1, model comparisons based on environmental issue type were utilized. Constrained regression weights were used to assess invariance between all paths in the model (Marcoulides et al, 2008) and a model with bootstrapping of 5,000 samples and 95% bias-corrected confidence intervals was examined, χ 2 ¼ 121.328, df ¼ 102, p ¼ 0.093, RMSEA ¼ 0.022, CFI ¼ 0.991, 90% CI: 0.000-0.035. A χ 2 difference test revealed that the test for differences between environmental issue types χ 2 difference ¼ 33.953, df ¼ 24, po0.05 indicated that the regression weights within the model were not invariant for environmental issue type.…”
mentioning
confidence: 99%
“…As a result, for each successive model (depicted in Appendix H), the  was not significant (p<.05), and the CFI was less than 0.01. According to the research of Qureshi and Compeau (2009), and Marcoulides et al (2008), a nonsignificant  and CFI below 0.05 suggests model invariance, indicating that imposing these constraints did not worsen the model fit significantly.…”
Section: Between-group Analysis Of Knowledge Orchestration Performance In Entrepreneurial Start-up and Growth Stagesmentioning
confidence: 99%